Physicochemical Analysis And Minerals Content Of Two Varieties Of Hibiscus Sabdariffa Seeds From Benin. - Akabassi, Blandine; BOTHON, FIFA THEOMAINE DIANE; ADOVELANDE, JACQUES; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2016)
Hibiscus sabdariffa Linn. (Malvales) varieties are widely used in sub-Saharan Africa as plant food and in folk medicine. Several studies have focused on the variety sabdariffa of different countries; but the one that from Benin has not been investigated. The present study has evaluated some physicochemical characteristics and mineral content of two varieties of Hibiscus sabdariffa seeds from Benin. The Physicochemical analysis result obtained were as follows:96.12 ± 0.17 and 96.19 ± 0.05% of dry matter, 5.40 ± 0.40and 4.94 ± 0.10% of ash, 4.69 ± 0.07 and 2.31 ± 0.02% of crude proteins, 0.7l ± 0.03 and 1.09 ± 0.05 mg/ml of vitamin C respectively for sabdariffa and altissima varieties seeds. Spectroscopy used for mineral analysis revealed in the two seeds varieties:43.10 ± 0.003 and 71.68 ± 0.002% of manganese, 12.91 ± 0.002 and 9.89 ± 0.17mg/kg of copper, 128.54 ± 0.40 and 85.08 ± 0.12 mg/kg of iron , 44.47 ± 0.60 and 16.24 ± 0.06mg/kg nickel, 231.53 ± 0.2 and 440.51 ± 0.58mg/kg sodium, 61.44± 0.57and 45.94 ± 0.04 mg/kg zinc. Following the above results, Hibiscus sabdariffa variety altissima and Hibiscus sabdariffa variety sabdariffa seeds can be used as food supplement or additive to resolve or prevent nutriments deficiency consequences.
Keywords: Hibiscus sabdariffa; variety; physicochemical characteristics; nutrients.